The mother–offspring dyad: microbial transmission, immune interactions and allergy development. (14th August 2017) - Jenmalm, M. C.
Abstract: The increasing prevalence of allergy in affluent countries may be caused by reduced intensity and diversity of microbial stimulation, resulting in abnormal postnatal immune maturation. Most studies investigating the underlying immunomodulatory mechanisms have focused on postnatal microbial exposure, for example demonstrating that the gut microbiota differs in composition and diversity during the first months of life in children who later do or do not develop allergic disease. However, it is also becoming increasingly evident that the maternal microbial environment during pregnancy is important in childhood immune programming, and the first microbial encounters may occur already in utero . During pregnancy, there is a close immunological interaction between the mother and her offspring, which provides important opportunities for the maternal microbial environment to influence the immune development of the child. In support of this theory, combined pre‐ and postnatal supplementations seem to be crucial for the preventive effect of probiotics on infant eczema. Here, the influence of microbial and immune interactions within the mother–offspring dyad on childhood allergy development will be discussed. In addition, how perinatal transmission of microbes and immunomodulatory factors from mother to offspring may shape appropriate immune maturation during infancy and beyond, potentially via epigenetic mechanisms, will be examined. Deeper understanding of these interactions between the maternal and offspring microbiome and immunity is needed to identify efficacious preventive measures to combat the allergy epidemic.